BALANCING, PROPORTIONALITY AND THE “ONE RIGHT ANSWER” IN THE ARGUMENTATIVE PRACTICE OF THE BRAZILIAN SUPREME COURT - SEVERAL PATHS TO NORMATIVE CORRECTION? THE CASE OF HATE SPEECH - Rodrigues, Guilherme Scotti; de Carvalho Netto, Menelick (Direito.UnB - Revista de Direito da Universidade de Brasília, 2022)
The axiological theory of fundamental rights reached in the last decades great academic and institutional repercussion in Latin America, including Brazil. It is commonly called a ‘post-positivist’ theory but, by rejecting Dworkin's thesis of ‘the one right answer’ it maintains elements that, as we argue, are typical of legal positivism. We herein discuss if, in light of a deontological theory of rights a correct decision would be possible, even if based on axiological terms of value-weighting. The rationale for a decision expressed in terms of conflicts of rights reduces the indispensability of fundamental rights. We argue, however, that this does not, of itself, prevent the decision taken from being correct. We use as an example the decision in which the Brazilian Supreme Court discussed whether the constitutional provision that no statute of limitations applies to the crime of racism could be extended to the publication of anti-Semitic hate speeches. Referring to the ideas of balancing and proportionality the court concluded that, under Brazilian law, anti-Semitic hate speech constitutes the crime of racism. We maintain that such a decision proves to be the only correct one under Brazilian Law in the deontological sense. Despite the argumentative damage brought to the internal debate of the courts on the role of fundamental rights, such decisions can nevertheless be able to discern, in the concrete cases, the legitimate from the abusive claims, so as to enable the Law to consistently confront the tendency to abusive and merely instrumental use of the Law itself.